Pszichológiai tanácsadás - online - Kinga Bakk-Miklósi (Symbolon)
Psychological Counseling – Online The period of online education rewrote the teacher-student relationship, the teaching methods, content, tools, etc. of course, it also extended to online counseling, which, in addition to overcoming initial objections, proved to be extremely useful. This study is about the sharing of the most important experiences, it tries to answer how we used the online space and social media in psychological counseling as a helper.